Dual RNA-Seq Uncovers Metabolic Amino Acids Dependency of the Intracellular Bacterium Piscirickettsia salmonis Infecting Atlantic Salmon - Valenzuela-Miranda, Diego; Gallardo-Escárate, Cristian (Frontiers in Microbiology, 2018)
High-throughput sequencing technologies have offered the possibility to understand the complexity of the transcriptomic responses of an organism during a wide variety of biological scenarios, such as the case of pathogenic infections. Recently, the simultaneous sequencing of both pathogen and host transcriptomes (dual RNA-seq) during the infection has become a promising approach to uncover the complexity of the host–pathogen interactions. In this study, through a double rRNA depletion and RNA sequencing protocols, we simultaneously analyzed the transcriptome of the intracellular bacterium Piscirickettsia salmonis and its host the Atlantic salmon (Salmo salar) during the course of the infection. Beyond canonical host immune-related response and pathogen virulent factors, both bacteria and host displayed a large number of genes associated with metabolism and particularly related with the amino acid metabolism. Notably, genome-wide comparison among P. salmonis genomes and different fish pathogens genomes revealed a lack of the biosynthetic pathway for several amino acids such as valine, leucine, and isoleucine. To support this finding, in vitro experiments evidenced that when these amino acids are restricted the bacterial growth dynamics is significantly affected. However, this condition is phenotypically reversed when the amino acids are supplemented in the bacterial growth medium. Based on our results, a metabolic dependency of P. salmonis on S. salar amino acids is suggested, which could imply novel mechanisms of pathogenesis based on the capacity to uptake nutrients from the host. Overall, dual transcriptome sequencing leads to the understanding of host–pathogen interactions from a different perspective, beyond biological processes related to immunity.